The Role of Pesantren as Traditional Islamic Education Institutions in the Digital Era - Sahri; Aziz, Su'udin (Al Hikmah: Jurnal Studi Keislaman, 2023)
Pesantren is a traditional Islamic educational institution that has been established since ancient times in Indonesia. In facing the challenges of modern times, pesantren play an important role in maintaining the identity and sustainability of Islamic values. However, with the advent of the digital era, pesantren are faced with various changes and new challenges.. The method used in this study is library research through a qualitative research approach. Theoretically, this study traces various literature, books and scientific articles in accordance with the theme of the study, then interpreted with existing conditions. The result of this study is that the role of pesantren as traditional Islamic educational institutions in the digital era contains challenges and opportunities. By blending traditional values and technological advancements, pesantren can continue to contribute effectively in teaching and maintaining Islamic values in modern life. The wise use of technology will have a positive impact on Islamic education in pesantren and ensure the continuity of this institution in spreading pure Islamic values in the increasingly advanced digital era